2000
DOI: 10.1111/1468-5957.00356
|View full text |Cite
|
Sign up to set email alerts
|

Value Relevance of Mandated Comprehensive Income Disclosures

Abstract: This study provides some market based evidence on the usefulness of comprehensive income disclosures in a Statement of Changes in Equity (SCE). Using a sample of listed New Zealand firms, we find no evidence that separate disclosure of the comprehensive income items provides any value relevant information above and beyond the aggregate comprehensive income figure. Likewise, in the post-SCE period, we find no evidence of an increase in the incremental value relevance of the comprehensive income items over net i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 21 publications
7
113
0
10
Order By: Relevance
“…The price regression model is likely to be affected by scale effects (Wu and Xu, 2008;Easton and Sommers, 2003), which can be mitigated by deflating all variables by the market value of the previous period (Barth et al, 2008;Lang et al, 2006;Aboody et al, 2002;Cahan, 2000;Brown et al, 1999;Easton, 1998). Moreover, according to Ali et Hwang (2000), the deflation of both dependent and independent variables is expected to control for heteroscedasticity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The price regression model is likely to be affected by scale effects (Wu and Xu, 2008;Easton and Sommers, 2003), which can be mitigated by deflating all variables by the market value of the previous period (Barth et al, 2008;Lang et al, 2006;Aboody et al, 2002;Cahan, 2000;Brown et al, 1999;Easton, 1998). Moreover, according to Ali et Hwang (2000), the deflation of both dependent and independent variables is expected to control for heteroscedasticity.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, (M1) is extended to include also the Other Comprehensive Income components (Cahan et al, 2000) and it is specified as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using sample firms operating in New Zealand, Cahan et al (2000) report that comprehensive income is much more relevant than net income and the individual components of comprehensive income do not provide value relevant information to the users of financial statements. Kanagaretnam et al (2009) investigate whether the components of other comprehensive income reported by Canadian firms have value relevance.…”
Section: The Background Of Comprehensive Income Reporting and Past LImentioning
confidence: 99%
“…However, non-normal distributions are common in financial ratios (Barnes, 1982:51;Deakin, 1976:95;So, 1987:488). They are especially common in smaller stock markets with a wide range of small-cap, mid-cap and large-cap companies, such as the JSE (Cahan, Courtenay, Gronewoller & Upton, 2000:1296. To confirm the robustness of the VAHU analysis, a high-level supplementary test was performed using similar methodology but alternative measures of human capital performance -i.e.…”
Section: Hce In South African Listed Companies Increased For the Finamentioning
confidence: 99%